Single-cell atlas of murine adrenal glands reveals immune-adrenal crosstalk during systemic Candida albicans infection - Zhang, Kai; Hu, Yuzhe; Li, Ruoyu; Li, Ting (Frontiers in Immunology, 2022)
Fungal sepsis remains a major health threat with high mortality, where the adrenal gland stress response has been rarely reported. Candida albicans (C.albicans) is the most common opportunistic fungal pathogen of life-threatening disseminated candidiasis and fungal sepsis. In the present study, we performed single-cell RNA sequencing (scRNA-Seq) using the 10x Genomics platform to analyze the changes in murine adrenal transcriptome following systemic C.albicans infection. A total of 16 021 cells were categorized into 18 transcriptionally distinct clusters, representing adrenocortical cells, endothelial cells, various immune cells, mesenchymal cells, smooth muscle cells, adrenal capsule, chromaffin cells, neurons and glials. As the main cell component in the adrenal gland responsible for steroidogenesis, the adrenocortical cells dramatically diminished and were further grouped into 10 subclusters, which differently distributed in the infected and uninfected samples. Pseudo-time analysis revealed transitions of the adrenocortical cells from the initial normal states to active or dysfunctional states following systemic C.albicans infection via two trajectory paths. Endothelial cells in the highly vascularized organ of adrenal gland further proliferated following infection, with the upregulation of genes positively regulating angiogenesis and downregulation of protective genes of endothelial cells. Immune cells were also excessively infiltrated in adrenal glands of C.albicans-infected mice. Macrophages dominated the immune microenvironments in murine adrenal glands both before and after C.albicans infection, mediating the crosstalk among the steroid-producing cells, endothelial cells and immune cells within the adrenal gland. NLR family, pyrin domain containing 3 (NLRP3, encoded by Nlrp3) and complement receptor 3 (CR3, encoded by Itgam) were found to be significantly upregulated on the adrenal macrophages upon systemic C.albicans infection and might play critical roles in mediating the myeloid response. Meanwhile, the number and strength of the interactions between the infiltrating immune cells and adrenal resident cells were unveiled by cell-cell communication analysis to be dramatically increased after systemic C.albicans infection, indicating that the immune-adrenal crosstalk might contribute to the compromised functions of adrenal cells. Overall, our comprehensive picture of the murine adrenal gland microenvironment in systemic C.albicans infection provides deeper insights into the immune-adrenal cell communications during fungal sepsis.